Burkina Faso : Staff Report for the 2005 Article IV Consultation, Fourth Review Under the Poverty Reduction and Growth Facility Arrangement, and Request for Waiver of Performance Criterion. (IMF Staff Country Reports; Country Report ;, 2005)
The staff report for the combined 2005 Article IV Consultation on Burkina Faso focuses on recent economic developments and performance. Burkina Faso has maintained an average real GDP growth rate of more than 6 percent annually, and inflation has been contained. Revenues performance is benefiting from the computerization of the major customs offices and the introduction of a new single taxpayer identification number. Continued implementation of pro-growth macroeconomic policies, diversification of the economy, and structural reforms will be necessary to establish the conditions for a resumption of robust economic growth.